Comparison of Malaysian urban green spaces use prior and during the COVID-19 pandemic and preferences for post-pandemic design improvements - Mohd Razali, Iskandar Al Khalifah; Abd. Shukor, Shureen Faris (Planning Malaysia, 2022)
A survey on the comparison between Malaysians’ usage of green spaces prior and during COVID-19 pandemic was conducted using an online self-administered questionnaire. Frequency and descriptive analysis were applied and a total of 415 responses from the whole Malaysia was recorded. Results showed that there was a huge increase in the number of respondents who did not visit the urban green spaces during COVID-19 pandemic. In addition, there was an increase in the use of home garden and neighbourhood park during the pandemic as compared to before the COVID-19 pandemic. The majority of the respondents involved in the survey mentioned that they diverted their visitation to the nearest green spaces available during the pandemic. The findings managed to highlight the changes in usage pattern of green spaces among Malaysians and provide proposals to relevant authorities on the future design of parks and green spaces in post-COVID-19 settings.